EFL TEACHERS’ ATTITUDES TOWARD THE INTERNALIZATION OF ARTIFICIAL INTELLIGENCE TOOLS IN SPEAKING LEARNING ACTIVITIES - Kristian Florensio Wijaya (Widya Mandala Surabaya Catholic University, 2025)
ABSTRACTEFL teachers should not solely rely on their regular classroom learning activities on conventional pedagogical approaches but also the optimum utilization of technological-based learning platforms. One can potentially experience this through the meaningful internalization of artificial intelligence tools as a further attempt to promote better-facilitated second-language classroom learning dynamics. This small-scale library study was initiated to investigate EFL teachers’ attitudes toward the internalization of artificial intelligence tools in their regular speaking learning activities. To achieve this main study objective, the researcher capitalized on a thematic analysis while analyzing the findings from 30 previous artificial intelligence journal articles. With the support of a thematic analysis, the researcher is more likely to yield more robust, systematic, and understandable results as each finding was clustered into identical research themes. The thematically categorized findings revealed that EFL teachers inculcated positive attitudes toward the internalization of artificial intelligence tools as these technological platforms evoked a comfortable speaking learning atmosphere and transfigured learners into competent target language speakers.Keywords: Artificial intelligence; second language learning; teachers’ attitudes; library study; thematic analysis